Utilidad de la cámara de Gesell en el desarrollo de las competencias profesionales del Psicólogo en la Universidad Técnica de Machala - Salamea Nieto, Rosa Marianela (2015)
As part of the accreditation process of the undergraduate, the Organic Law on Higher Education (2010) Art. 13, states that are functions of the higher education system to provide optimum levels of quality in training and research. Similarly, the Academic Regime Regulations (2010) states that a bachelor’s degree, must train professionals to analyze, plan, manage and evaluate models and intervention strategies in professional fields associated with basic social, educational sciences, Health humanities and arts. From the pedagogical approach is a resource skills training with emphasis on efficiency, equity and quality. It refers to what people should be able to do to achieve professional success. With regard to the training of psychologists, the use of camera Gesell is a useful element to develop the skills of academic and practical training, with an organi¬zed what is sought from each subject reach criterion. Evaluate and develop the skills, it does not mean that people do not have or do not have them in absolute terms, but dominate in different degrees, hence develop the skills to be achieved by the theoretical and practical knowledge. The current study aims to demonstrate the usefulness of the camera Gesell on the development of professional skills of the psychologist integrating theoretical knowledge with practice, also it analyzes the development of general and specific skills according to the content required for professional accreditation. As an assessment tool uses a Likert type of skills that meet the requirements of the discipline and society in terms of preparing for the labor market scale. This in¬ventory competences are described as reference points for curriculum improvement of the curriculum of the psychology at the Technical University of Machala.